„Read the edge”: Acrostics in Virgil’s Sinon Episode - Adkin, Neil (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Virgil’s famous Sinon episode at the start of Aeneid II contains four hitherto unidentified acrostics. Examination of these particular instances sheds light on Virgil’s acrostical practice in general.